Online Class Interaction In Teaching And Learning Process At Third Grade Students Of Sekolah Dasar Islam Terpadu Samarinda - Ahyu Ningtyas; Rahmat Soe'oed; Syamdianita (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
The purpose of the study is to know the types of classroom interaction and the teachers interact to students in English lesson. This research was conducted in SD IT Insan Karim Samarinda Seberang. This study focused on types of classroom interaction such as : (1) Teacher – student, (2) Student – teacher and (3) Student – student. The design of this study was qualitative study which to illustrate the types used in classroom interaction. Research subject was chosen through purposive sampling resulting one subject to be analyzed.The subject was an English teacher and her students from SD IT Insan Karim Samarinda Seberang who has more than one a half years teaching experiences. There were two research instruments used in this study. They are observation and interview. The data were taken from 2 English teaching video which were transcribed. The collected data were classified into three types of classroom interaction. Afterward the researcher triangulated the data by crosschecking the data related to data she acquired from interview. The result of the study showed the English teacher and her students in third grade students of SD IT Insan Karim Samarinda Seberang used three types of classroom interaction : Teacher – student , student - teacher and student – student. While the data from interview showed that the teacher help the student to do interaction related the topic. But, the result from observation and interview were not same because English teacher only said about teacher centered and student centered in interview.